MicroRNA-155 Implication in M1 Polarization and the Impact in Inflammatory Diseases - Pasca, Sergiu; Jurj, Ancuta; Petrushev, Bobe; Tomuleasa, Ciprian; Matei, Daniela (Frontiers in Immunology, 2020)
Macrophages are known to have an impact in cytokine signaling in the myriad of organs in which they reside and are classically known to be either pro-inflammatory (M1), anti-inflammatory (M2). Different classes of signaling molecules influence these states, of which, microRNAs represent key modulators. These are short RNA species approximately 21 to 23 nucleotides long that generally act by binding to the 3′ untranslated region of mRNAs, regulating their translation, and, thus, the quantity of protein they encode. From these species, microRNA-155 was observed to be of great importance for M1 polarization. Because of it’s major implication in M1 polarization microRNA-155 was shown to be implicated in different inflammatory diseases. To name a few, microRNA-155 was shown to be modified in patients with asthma and to correlate with asthma symptoms in mouse model; it has been shown to modulate the activity of foam cells and influence the dimensions of the atherosclerotic plaque and it has also been shown to be of crucial influence in transducing the signal of LPS in septic shock. Because of this, the current review aims to offer an overview of the role of microRNA-155 in M1 polarization, the implication that this poses for the pathophysiology of inflammatory diseases and the potential therapeutic possibilities that this knowledge might bring. Currently, microRNA-155 has been used in clinical trials as a marker of inflammation, but the question remains if it’s inhibition will be useful in inflammatory diseases, as other products might have a better cost/benefit ratio.